2022
DOI: 10.1111/add.15966
|View full text |Cite
|
Sign up to set email alerts
|

Prices, taxes and alcohol use: a systematic umbrella review

Abstract: Aim To measure the impact of taxes and prices on alcohol use with particular attention to the different context of rising alcohol consumption in low‐ and middle‐income countries. Methods Systematic review: we searched MEDLINE, Embase, EconLit and LILACS, grey literature, hand‐searched five specialty journals and examined references of relevant studies. We considered all reviews that included studies that quantitatively examined the relationship between alcohol prices or taxes and alcohol use. At least two revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Recent analyses (e.g., [ 32 ]) showed marked underestimation of the beneficial effects of taxation using the standard elasticities from meta-analyses conducted a decade ago [ 23 , 24 , 25 , 27 ] when compared with direct estimates of interrupted time-series analyses. However, more recent meta-analyses showed similar values [ 33 ]. Finally, all models were based on relative risks derived from meta-analyses for dose–response relationships [ 34 ], and these could pose challenges when applied to reductions in drinking and its consequences.…”
Section: Discussionmentioning
confidence: 83%
“…Recent analyses (e.g., [ 32 ]) showed marked underestimation of the beneficial effects of taxation using the standard elasticities from meta-analyses conducted a decade ago [ 23 , 24 , 25 , 27 ] when compared with direct estimates of interrupted time-series analyses. However, more recent meta-analyses showed similar values [ 33 ]. Finally, all models were based on relative risks derived from meta-analyses for dose–response relationships [ 34 ], and these could pose challenges when applied to reductions in drinking and its consequences.…”
Section: Discussionmentioning
confidence: 83%
“…Importantly, we found that high‐level and very‐high‐level drinkers, who constituted less than 10% of all drinkers, were likely to drink over half of total volume of beer, coolers and liquor consumed by all adult drinkers. A large body of literature has demonstrated the effectiveness of alcohol price and tax increases in reducing alcohol consumption [33] and alcohol‐related morbidity and mortality [34]. Heavy drinkers are more likely to purchase cheaper alcohol than other drinkers [35] and to show the steepest decline in consumption levels when prices increase given their high baseline consumption [36].…”
Section: Discussionmentioning
confidence: 99%
“…Excise taxes for alcohol are a powerful tool to do so. Increased tax has been shown to be associated with reductions in consumption, 47 attributable harm, 48 and marked reductions in cirrhosis mortality 49 . The impact of taxation ultimately depends on the degree of price increase, with a 3% to 7% reduction in consumption expected with every 10% increase in the price of alcohol-associated beverages, and are similar across low-income, middle-income, and high-income countries 47 .…”
Section: Interventions To Reduce Alcohol Usementioning
confidence: 99%
“…Increased tax has been shown to be associated with reductions in consumption, 47 attributable harm, 48 and marked reductions in cirrhosis mortality 49 . The impact of taxation ultimately depends on the degree of price increase, with a 3% to 7% reduction in consumption expected with every 10% increase in the price of alcohol-associated beverages, and are similar across low-income, middle-income, and high-income countries 47 . A WHO study 50 on the potential of increasing taxation in 16 countries spanning low-income, middle-income, and high-income settings indicated that increasing current alcohol taxes by 50% had low costs (< International $0.10 per capita) and a highly favorable cost-to-effect ratio (< International $100 per healthy life year gained in both low-income and high-income settings).…”
Section: Interventions To Reduce Alcohol Usementioning
confidence: 99%